Inadequate Care during the Management of Type-2 Diabetes Mellitus: Prevalence and Associated Characteristics - Zakirullah Khan, Muhammad Afzal, Khalid Usman, Abdul Moiz Bhatti, Muhammad Aleem Uddin, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Type-2 diabetes mellitus (T2DM) is a chronic metabolic disorder marked by insulin resistance, progressive beta- cell dysfunction, and hyperglycemia, representing one of the most prevalent non-communicable diseases worldwide. Objective: The main objective of the study is to find inadequate care during the management of type-2 diabetes mellitus: prevalence and associated characteristics. Methodology: This cross-sectional study was conducted at Hayatabad Medical Complex, Peshawar, Pakistan during March 2022 to June 2023. Data include 220 patients suffering from type II DM. Demographic data included age, gender, education level, occupation, and socioeconomic status. Demographic and clinical variables included the duration of diabetes, co-morbid conditions like hypertension, dyslipidemia, HbA1c levels, and complications of diabetes were documented. Results: A total of 220 patients with type-2 diabetes mellitus (T2DM) participated in the study. The mean age of participants was 52.4 years (SD ± 10.6), with 55% being female and 45% male. The majority of patients (62%) were from middle-income households, and 48% had completed secondary education or higher. The average duration of diabetes was 8.3 years (SD ± 5.1), and 72% of patients reported at least one comorbidity, such as hypertension (54%) or dyslipidemia (39%). Poor dietary practices were the most prevalent issue, affecting 64% of patients, followed by low medication adherence at 57%. Systemic barriers also played a significant role, with 45% experiencing difficulty accessing healthcare, 22% facing financial barriers, and 18% reporting limited availability of medications. Conclusion: It is concluded that inadequate care in type-2 diabetes mellitus management remains a significant challenge, driven by poor glycemic control, behavioral and psychosocial barriers, and systemic limitations in healthcare access. Keywords: Patients, Type II DM, Dietary, Medication, Demographic, Hypertension